“Implementación de un control automático de temperatura para el secado de cacao en un invernadero de la parroquia Guasaganda del cantón La Maná”. - Cuasquer Salazar, Christian Camilo (2020)
The main objective of this project was to implement an automatic temperature and humidity control system using a logic module called LOGO for drying cacao in a greenhouse in Guasaganda parish in La Maná canton. This system was created because of the problems that exist in cacao beans drying techniques due to climatic conditions which lengthen the drying time with the risk of the appearance of mold on the product, thus, reducing significantly the selling price. The purpose of drying process is to reduce the moisture-content of the beans. To execute the project, the necessary information was collected to identify the parameters that influence the drying of cacao beans; two of these parameters were: temperature and humidity in the recinto, so once the variables had been identified; the electrical, electronic, and electromechanical components were identified. Then, the control system was designed by using programs such as CADe_SIMU for designing the control and power circuit and LOGO soft Comfort V8 for programming it. Lastly, the implementation of the elements which define the automatic control system. In conclusion, the automatic control system achieves an adequate drying, so improving the drying process of cacao beans and obtaining a quality of the product that complies with technical requirements according to INEN 176 standard. Through this control system, the user can have direct access to the MT-530E controller where temperature and humidity can be configured, creating a desired menu. The field tests gave accurate data, reaching temperatures from 35 °C to 50 °C, also verifying that its economic viability is positive and giving an IRR of 118 % and a NPV more than 0 which shows that the project is executable.